Impact of objectively-measured sleep duration on cardiometabolic health: A systematic review of recent evidence - Dejenie, Tadesse Asmamaw; G/Medhin, Markeshaw Tiruneh; Admasu, Fitalew Tadele; Adella, Getachew Asmare; Enyew, Engidaw Fentahun; Kifle, Zemene Demelash; Seid, Mohammed Abdu; Mengstie, Misganaw Asmamaw; Abebe, Endeshaw Chekol (Frontiers in Endocrinology, 2022)
Sleep disorders and cardiometabolic diseases are both on the rise in the world today. The most common sleep disturbances include reduced sleep duration, insomnia, disordered circadian rhythm, and obstructive sleep apnea. Cardiometabolic disease is a spectrum of diseases, including cardiovascular disease, metabolic syndrome, and type 2 diabetes mellitus. To date, sleep has emerged as a potential target for cardiometabolic disease prevention. Recently, several epidemiological studies have provided ample evidence that objective measured short sleep duration increases the risk of cardiometabolic disease. However, the findings are inconsistent, and few studies measure sleep duration on cardiometabolic profiles objectively. Therefore, in this review, we focused on the recently published literature that explored the association between objectively measured sleep duration and cardiometabolic profiles (cardiovascular diseases, type 2 diabetes mellitus, and metabolic syndrome), seeking more insights regarding the applicability and, in turn, the impact of objectively measured sleep duration on cardiometabolic health, which is relatively understudied. In this review we found that A U-shaped relationship between objectively measured sleep duration and the risk of cardiometabolic disease has been found in several studies, indicating that short sleep durations increase cardiometabolic risks In the general, the association between objectively measured sleep insufficiency and increased cardiometabolic risks (CMR) has been well-documented in higher-income countries. In this review, we found a U-shaped relationship between objectively measured sleep duration and the risk of cardiometabolic disease, indicating that objectively measured short sleep durations increase cardiometabolic risks. In general, the association between objectively measured sleep duration and increased cardiometabolic risks (CMR) has been well-documented in higher-income countries. Several studies found that longer sleep duration was associated with a more favorable cardiometabolic profile in early adolescence, independent of other risk factors. On the other hand, objectively measured short sleep duration is associated with adverse cardiometabolic health outcomes such as coronary heart disease, hypertension, type 2 diabetes mellitus, and metabolic syndrome.